Bortezomib a safety treatment for patients with Multiple Myeloma and Cystic Fibrosis - Fabiana Gentilini; Anna Levi; Vincenzo Federico; Eleonora Russo; Robin Foà; Maria Teresa Petrucci (Mediterranean Journal of Hematology and Infectious Diseases, 2012)
Introduction: Bortezomib is a proteasome inhibitor that targets myeloma cell and its bone marrow micro-environment. Intravenous Bortezomib (1.3 mg/m2 administered on days 1,4,8 and 11 of a 21 day cycle), with or without dexamethasone, is effective and well tolerated in patients with relapsed/refractory multiple myeloma (MM). Methods: We treated a MM patient with Cystic Fibrosis with Bortezomib alone to avoid the use of corticosteroid and consequently the risk of lung infection reactivations, first of all due to the patient Pseudomonas aeruginosa colonization. Bortezomib was administrated at 1.3 mg/m2 on days 1,4,8 and 11 with a 10 day rest period and four 21-day cycles were administered. We evaluate the treatment response and toxicity. Results: After four cycles of therapy the patient achieved a very good partial response (VGPR) according to the IMWG response criteria, without clinically significant side effects. Conclusions: Bortezomib can be successfully utilized for the management of this difficult disease situation